La-Fe-Si-based magnetic refrigeration material and preparation method thereof
By forming a porous structure of NaZn13 type crystal structure and pores in La-Fe-Si-based magnetic refrigeration material, the problems of poor mechanical properties and insufficient thermal conductivity after hydrogenation are solved, and efficient magnetothermal effects and thermal conductivity are achieved.
Patent Information
- Application Number
- CN202310770043.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-27
- Publication Date
- 2024-12-27
AI Technical Summary
The existing La-Fe-Si-based magnetic refrigeration materials are prone to lattice expansion and cracks after hydrogenation, resulting in poor mechanical properties and reduced magneto-thermal effects, and thermal conductivity is not sufficient to meet the requirements of high-efficiency magnetic refrigeration machines.
The porous structure consisting of La(Fe,Si)13-based phase and pore units with NaZn13 crystal structure is formed by melting, crushing, hot pressing and annealing to form a magneto-heat phase integrated structure, and the porosity is controlled between 0% and 20%. , ensure the continuity of the magneto-heat phase and the formation of thermal conductivity channels.
The low magnetic field-driven large magneto-thermal effect, excellent mechanical properties and high thermal conductivity of La-Fe-Si-based magnetic refrigeration material are achieved, ensuring that the mechanical properties of the material are improved after hydrogen filling, without obvious cracks on the appearance and improved thermal conductivity.
Smart Images

Figure CN119207930A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a magnetic refrigeration material, in particular to a La-Fe-Si based magnetic refrigeration material, belonging to the field of magnetic refrigeration materials. Background Art
[0002] The most commonly used refrigeration method at present is gas compression refrigeration, which has problems such as low efficiency, high energy consumption and environmental friendliness. Therefore, a new refrigeration technology is urgently needed to replace traditional compression refrigeration. Among many new refrigeration technologies, magnetic refrigeration has attracted widespread attention due to its advantages of high efficiency and energy saving, green environmental protection, and low vibration and noise of refrigeration equipment.
[0003] The research on magnetic refrigeration in the low temperature zone is relatively mature and has been put into practical use, becoming one of the important ways of low temperature refrigeration. However, magnetic refrigeration technology in the near-room temperature zone is still in the research and development stage and has not yet been commercialized. Common room temperature magnetic refrigeration materials mainly include: metal Gd, Gd-Si-Ge based alloys, Mn-Fe-P based alloys, Mn-As-Sb based alloys and La-Fe-Si based alloys. Among them, La-Fe-Si based alloys are recognized as one of the most likely materials to be widely used in room temperature magnetic refrigerators because of their low cost, significant magnetocaloric effect, adjustable Curie temperature and no toxic elements. NaZn 13 Type crystal structure LaFe 13-x Si x The Curie temperature of a compound is usually around 200K. Interstitial atom (such as H, B, C) doping and / or element (such as Co, Ni, Al) substitution can increase the Curie temperature of the compound to room temperature. Among them, introducing H atoms into the interstitial of the compound is currently one of the most effective methods to increase the Curie temperature to above room temperature while maintaining its large magnetocaloric effect. However, La(Fe,Si) 13 The compound is inherently brittle, and the bulk material will inevitably expand its lattice after the introduction of interstitial H atoms, resulting in cracks and even turning into powder. In practical applications, high-efficiency magnetic refrigerators require not only a large magnetocaloric effect of the magnetic working fluid, but also the ability to quickly exchange heat with the fluid. Therefore, the magnetic refrigeration material needs to be processed into a shape with a strong heat exchange capacity (such as a sheet or sphere with a large specific surface area), and the magnetic refrigeration material itself is required to have good thermal conductivity, which poses a huge challenge to the processability and thermal conductivity of La-Fe-Si-based hydrides.
[0004] In order to enhance the mechanical and thermal conductivity of materials, polymer or metal bonding has become a common processing method for La-Fe-Si based materials in recent years. For example, the Chinese invention patent "Bonding La(Fe,Si) 13Based on magnetocaloric effect materials and their preparation methods and uses, the patent number of which is ZL201110374158.1 (the authorization announcement number is CN103137281B) discloses a bonded La(Fe,Si) 13 Based on magnetocaloric effect material, a small amount of polymer binder is introduced to obtain bonding La(Fe,Si) 13 Based on magnetocaloric effect material. This bonding material has good mechanical properties and can be used to prepare complex-shaped regenerators, but the polymer has poor thermal conductivity, resulting in generally low thermal conductivity of the composite material. 13 The base alloy hydrogenated particles are compounded with low melting point metal or alloy under heat and pressure, such as the Chinese invention patent "LaFeSi-based magnetic refrigeration composite material and its preparation method and application" with patent number ZL201510975703.0 (authorization publication number CN106906408B); or, prepared into a metal-bonded bulk composite material, and then subjected to hydrogen absorption treatment, such as the Chinese invention patent application "Metal-bonded hydrogenated La(Fe,Si) 13 Based on magnetic refrigeration sheet and its preparation method and application, its patent application number is CN201710845904.8 (patent publication number CN109524189A); it is found that this type of composite material has good mechanical properties and greatly improved thermal conductivity, but it is difficult to ensure that the two materials do not generate impurities when compounded; in addition, in addition to the dilution effect of the non-magnetocaloric phase, pressure will further break the magnetocaloric alloy particles, resulting in a significant reduction in the magnetocaloric effect of the composite material. Another example is the Chinese invention patent "Lanthanum iron silicon-based hydride magnetic working fluid and its preparation method, magnetic refrigerator", its patent number is ZL201610426134.9 (authorization announcement number is CN105957672B), the lanthanum iron silicon-based alloy ingot is subjected to high-temperature heat treatment under the protection of inert gas, and then the lanthanum iron silicon-based alloy particles after high-temperature heat treatment are hot pressed at 400-1100°C, and the hot pressed block alloy is subjected to hydrogen absorption treatment. The magnetic working fluid prepared by this invention has good mechanical properties, which solves the problem of poor mechanical properties such as pulverization and fragility of lanthanum iron silicon-based compounds after hydrogenation. However, hot pressing also causes further fragmentation of magnetocaloric alloy particles and even magnetocaloric phase decomposition, resulting in a serious reduction in magnetocaloric effect.
[0005] Therefore, it is necessary to further improve the existing La-Fe-Si based magnetic refrigeration materials to optimize the comprehensive performance of the materials so that they have high magnetocaloric effect, mechanical properties and thermal conductivity to meet the requirements of high-efficiency magnetic refrigerators. Summary of the invention
[0006] The first technical problem to be solved by the present invention is to provide a La-Fe-Si based room temperature magnetic refrigeration material with a large magnetocaloric effect driven by a low magnetic field, excellent mechanical and thermal conductivity properties, in response to the current status of the above-mentioned prior art.
[0007] The second technical problem to be solved by the present invention is to provide a method for preparing a La-Fe-Si based room temperature magnetic refrigeration material having a large magnetocaloric effect driven by a low magnetic field and excellent mechanical and thermal conductivity properties.
[0008] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: a La-Fe-Si based magnetic refrigeration material, comprising a plurality of magnetocaloric phase units and a plurality of pore units, characterized in that: the magnetocaloric phase is NaZn 13 La(Fe,Si) type crystal structure 13 The base phase, each of the magnetocaloric phase units is connected to form an integrated structure.
[0009] The above-mentioned integrated structure formed by magnetic and thermal connection means a structure without gaps, cracks, etc.
[0010] The La-Fe-Si based magnetic refrigeration material also includes a non-magnetocaloric phase unit. The La-Fe-Si based magnetic refrigeration material is composed of a magnetocaloric phase unit, a pore unit and a non-magnetocaloric phase unit. The non-magnetocaloric phase is one or more combinations of Fe, Fe alloy and rare earth alloy.
[0011] The NaZn 13 La(Fe,Si) type crystal structure 13 Base phase chemical formula: R x (Fe 1-a M a ) 13-y Si y A z , wherein R is selected from La only; or any one or a combination of two or more of Ce, Pr, Nd elements and La; M is selected from any one or a combination of two or more of Cr, Mn, Co, Ni, Al elements; A is selected from H; or one or a combination of two of B and C and H, x satisfies: x=1, y satisfies: 1≤y≤2, z satisfies: 0.1≤z≤3, a satisfies: 0≤a≤0.1.
[0012] According to the common technical knowledge in this field, the above NaZn 13 La(Fe,Si) type crystal structure 13 The general chemical formula of the base phase is defined, and each element and its content are strictly limited. The H element can make the magnetocaloric compound work near room temperature (i.e. 250-330K) and have a large magnetocaloric effect; Ce, Pr, and Nd elements replacing part of La can help enhance the magnetocaloric effect of the compound; Cr, Mn, Co, Ni, and Al elements replacing a small amount of Fe can help to accurately control the Curie temperature of the compound; B and C doping can help reduce the hysteresis loss of the compound. If the Si element content y is less than 1, the compound is difficult to exist stably; if the Si element content y is greater than 2, the magnetocaloric effect of the compound is very low.
[0013] In the La-Fe-Si based magnetic refrigeration material, the porosity P of the pores satisfies: 0<P<20%.
[0014] Preferably, 8%≤P≤12%.
[0015] In the implementation of the present invention, it is found that the more pores there are, the fewer cracks there are in the block sample after hydrogen charging. However, too many pores will cause the material density and entropy change per unit volume to decrease too much; at the same time, the heat conduction channels are reduced and the thermal conductivity is very low. Therefore, the present invention strictly limits the upper limit of porosity.
[0016] The La-Fe-Si based magnetic refrigeration material has a large magnetocaloric effect, high thermal conductivity and excellent mechanical properties, namely: the maximum volume entropy change under a 2T magnetic field change is ≥60mJ / cm 3 K, thermal conductivity at room temperature ≥3W / mK, flexural strength at room temperature ≥10MPa.
[0017] A technical solution adopted by the present invention to solve the above second technical problem is: a method for preparing the La-Fe-Si based magnetic refrigeration material, characterized in that it includes the following steps in sequence:
[0018] 1) According to R x (Fe 1-a M a ) (13-y)b Si y A z Chemical formula configuration raw materials; wherein R is selected from only La; or any one or a combination of two or more of Ce, Pr, Nd elements and La; M is selected from any one or a combination of two or more of Cr, Mn, Co, Ni, Al elements; A is selected from one or a combination of two of B and C, x satisfies: 0.8≤x≤1.2, y satisfies: 1≤y≤2, z satisfies: 0≤z≤0.5, a satisfies: 0≤a≤0.1, b satisfies: 1≤b≤2;
[0019] 2) smelting the above raw materials to form an alloy, and then crushing the alloy into particles;
[0020] 3) pressing the particles into a green body;
[0021] 4) Annealing the green body to obtain NaZn 13 Phase of type crystal structure;
[0022] 5) The annealed green body is subjected to hydrogen charging treatment.
[0023] Preferably, in step 3), the particle size d of the particles satisfies: 38 μm≤d≤150 μm.
[0024] It is found in the implementation of the present invention that if the particle size of the crushed particles is too small, it will not only easily cause oxidation, but also destroy the original alloy structure, resulting in the formation of NaZn after annealing. 13 The magnetocaloric phase fraction of the type structure is too small and the entropy change is low; if the particle size of the crushed particles is too large, the pores of the pressed body are too large and the number is too low, which has a poor effect on improving the mechanical properties of the hydride.
[0025] There are many parameters to choose from for pressing, but in order to reliably control the pores in the La-Fe-Si based magnetic refrigeration material, in step 3), preferably, pressing is performed in a high vacuum environment or in an inert atmosphere, the pressure is 100 to 1000 MPa, the hot pressing temperature is from room temperature to 600°C, and the holding time is 1 to 10 min.
[0026] Preferably, in step 4), the pressed body is annealed in a high vacuum environment or in an inert atmosphere at a temperature of 1000 to 1150° C. for 5 to 72 hours to form a NaZn 13 La(Fe,Si) type crystal structure 13 Base magnetocaloric phase.
[0027] Another technical solution adopted by the present invention to solve the above second technical problem is: a method for preparing the La-Fe-Si based magnetic refrigeration material, characterized in that it comprises the following steps in sequence:
[0028] 1) According to R x Fe 13-y Si y Chemical formula configuration raw materials; wherein R is selected from only La; or any one or a combination of two or more of Ce, Pr, Nd elements and La, x satisfies: 1≤x≤7, y satisfies: 1≤y≤10;
[0029] 2) smelting the above raw materials to form an alloy, and then crushing the alloy into particles;
[0030] 3) The above particles are used as intermediates and mixed with Fe powder and Si powder; or, mixed with Fe powder, Si powder and alloy powder according to R x (Fe 1-a M a ) (13-y)b Si y A zThe mixed powder is prepared according to the chemical formula, wherein the alloy powder is a binary or multi-element alloy powder composed of Fe and Cr, Mn, Co, Ni, Al, B, C, and Si; R is selected from La only; or any one or a combination of two or more of Ce, Pr, and Nd elements and La; M is selected from any one or a combination of two or more of Cr, Mn, Co, Ni, and Al elements; A is selected from one or a combination of two of B and C, x satisfies: 0.8≤x≤1.2, y satisfies: 1≤y≤2, z satisfies: 0≤z≤0.5, a satisfies: 0≤a≤0.1, and b satisfies: 1≤b≤2;
[0031] 4) pressing the mixed powder into a green body;
[0032] 5) Annealing the green body to obtain NaZn 13 Phase of type crystal structure;
[0033] 6) The annealed body is then subjected to hydrogen charging treatment.
[0034] Preferably, in step 3), R x Fe 13-y Si y The particle size d of the alloy particle intermediate is ≤38 μm.
[0035] There are many parameters to choose from for pressing, but in order to reliably control the pores in the La-Fe-Si based magnetic refrigeration material, in step 4), preferably, pressing is performed in a high vacuum environment or in an inert atmosphere, the pressure is 100 to 1000 MPa, the hot pressing temperature is from room temperature to 600°C, and the holding time is 1 to 10 minutes.
[0036] Preferably, the pressed material is annealed in a high vacuum environment or in an inert atmosphere at a temperature of 1000 to 1150° C. for 5 to 72 hours to form a NaZn 13 La(Fe,Si) type crystal structure 13 Base magnetocaloric phase.
[0037] The above two preparation methods are to melt La-Fe-Si based alloy (without NaZn 13 magnetocaloric phase with a type structure, no magnetocaloric effect, but with toughness of Fe alloy phase) - crushing - pressing to form a porous green body - annealing (forming NaZn 13The magnetocaloric phase of the structure is formed by high-temperature diffusion reaction, and the magnetocaloric phase forms an integrated structure and retains an appropriate amount of pores. The pore morphology and quantity are regulated by changing the particle size, pressing temperature and pressure, and annealing temperature and time to obtain La-Fe-Si based magnetic refrigeration materials with different porosities. Since the magnetocaloric phase forms an integrated structure, there are fewer defects on the interface, the magnetocaloric effect loss is small, and the integrated structure forms a heat conduction channel with strong thermal conductivity. The above preparation method overcomes the problem of directly pressing NaZn 13 When brittle magnetocaloric phase particles with a type structure or magnetocaloric particles form a block with auxiliary additives, a large number of cracks are introduced into the particles or further broken, resulting in low magnetocaloric effect and thermal conductivity.
[0038] Compared with the prior art, the advantages of the present invention are as follows: the present invention includes a magnetocaloric phase and pores in the La-Fe-Si based magnetic refrigeration material. The magnetocaloric phase units are connected to form an integrated structure. The existence of this integrated structure reduces the defects of the interface and can reduce the magnetocaloric and thermal conductivity losses. During hydrogen expansion, the pores act as a buffer to avoid the crushing of grains and grain phases due to extrusion, thereby achieving the purpose of hydrogen filling without crushing. Compared with the fully dense La-Fe-Si based magnetic refrigeration material, the porous material of the present invention has a significant improvement in mechanical properties after hydrogen filling, and there is no obvious crack in the appearance; compared with the open-pore La-Fe-Si based magnetic refrigeration material, the thermal conductivity is greatly improved. The La-Fe-Si based magnetic refrigeration material of the present invention is easy to process and prepare into a complex shape and high thermal conductivity regenerator. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The backscattered electron mode scanning electron microscope images of the La-Fe-Si based magnetic refrigeration materials prepared in Examples 1 and 2 of the present invention;
[0040] Figure 2 Thermomagnetic (MT) curves of the La-Fe-Si based magnetic refrigeration materials prepared in Examples 1 and 2 of the present invention under a magnetic field of 0.05 T;
[0041] Figure 3 The rising field isothermal magnetization (MH) curves of the La-Fe-Si based magnetic refrigeration materials prepared in Examples 1 and 2 of the present invention;
[0042] Figure 4 The entropy change curves of the La-Fe-Si based magnetic refrigeration materials prepared in Examples 1 and 2 of the present invention under different magnetic field changes are as a function of temperature;
[0043] Figure 5 Three-point bending load-displacement curves of the La-Fe-Si based magnetic refrigeration materials prepared in Examples 1 and 2 of the present invention. DETAILED DESCRIPTION
[0044] The present invention is further described in detail below with reference to the accompanying drawings.
[0045] Embodiment 1:
[0046] The general chemical formula of the La-Fe-Si based magnetic refrigeration material of this embodiment is: La 0.7 Ce 0.3 Fe 11.5 Mn 0.15 Si 1.35 H z .
[0047] Scanning electron microscope was used to observe the La-Fe-Si based magnetic refrigeration material of this embodiment before hydrogen charging. 0.7 Ce 0.3 Fe 11.5 Mn 0.15 Si 1.35 The microstructure of the sample, such as Figure 1 As shown in Figure 2, it can be seen that the sample is composed of multiple magnetocaloric phases, multiple pores and non-magnetocaloric phases. The magnetocaloric phase is NaZn 13 La(Fe,Si) type crystal structure 13 The base phase (gray area) is composed of magnetocaloric phases connected to each other to form an integrated structure. The volume fraction of the magnetocaloric phase is about 86%. The non-magnetocaloric phases of this embodiment are mainly α-(Fe, Mn, Si) (black area) and La-Ce-rich rare earth alloy (white area). It can be seen that the fine non-magnetocaloric phase is dispersed in the magnetocaloric phase. The density of the sample obtained by the Archimedean drainage method is 6.64g / cm 3 The porosity of the sample is 8%. The block sample of the porous structure still maintains its complete shape after being filled with hydrogen, and there is no obvious crack in the appearance.
[0048] The preparation method of the La-Fe-Si based magnetic refrigeration material comprises the following steps in sequence:
[0049] 1) Press La 0.7 Ce 0.3 Fe 11.5 Mn 0.15 Si 1.35 The chemical ingredients are loaded into the crucible of the vacuum induction rapid solidification furnace, and then filled with high-purity argon gas after evacuation. When the temperature rises to the point where the raw materials are completely melted and the alloy melt is uniform, the alloy liquid is poured onto a rotating copper roller to form an alloy sheet;
[0050] 2) Mechanically crushing and screening the alloy flakes prepared in step 1);
[0051] 3) Pour the powder with a particle size of 75-150 μm screened in step 2) into a mold, place the mold in the center of the induction heating coil of a vacuum hot press, and evacuate to 5×10 -2Pa or less, hot pressing is carried out at a hot pressing temperature of 600°C and a hot pressing pressure of 400MPa;
[0052] 4) Heat-press the La 0.7 Ce 0.3 Fe 11.5 Mn 0.15 Si 1.35 The green body is placed in a quartz tube, which is then evacuated, filled with argon gas, and sealed;
[0053] 5) Place the sealed quartz tube in step 4) into an annealing furnace, heat to 1050°C, and anneal for 3 days to form a NaZn 13 La-type magnetocaloric phase 0.7 Ce 0.3 Fe 11.5 Mn 0.15 Si 1.35 alloy;
[0054] 6) The NaZn prepared in step 5) 13 La-type magnetocaloric phase 0.7 Ce 0.3 Fe 11.5 Mn 0.15 Si 1.35 The alloy was filled with hydrogen to saturation in a hydrogen atmosphere at 300°C and 0.2 MPa to obtain a porous La-Fe-Si-based magnetic refrigeration material La 0.7 Ce 0.3 Fe 11.5 Mn 0.15 Si 1.35 H z Hydride.
[0055] Physical performance test:
[0056] 1. The porous La-Fe-Si-based magnetic refrigeration material La obtained in step 6) was measured using a superconducting quantum interference vibrating sample magnetometer MPMS (SQUID) VSM 0.7 Ce 0.3 Fe 11.5 Mn 0.15 Si 1.35 H z Thermomagnetic (MT) curves of hydrides and isothermal magnetization (MH) curves at different temperatures. Figure 2 It can be seen that the Curie temperature of the material is 292K. Figure 3 As shown in the figure, near the Curie temperature, the sample magnetization curve has an obvious inflection point, showing a first-order paramagnetic to ferromagnetic magnetic transition. According to Maxwell's relationship:
[0057]
[0058] The entropy change under different temperature and magnetic field changes is calculated from the rising field isothermal magnetization curve. Figure 4 It can be seen that low magnetic field can cause the porous material to produce a large entropy change. The maximum mass entropy change under 0-1T and 0-2T magnetic fields is 12.6J / kgK and 15.1J / kgK respectively. It is further obtained that the maximum volume entropy change under 0-1T and 0-2T magnetic fields is 84mJ / cm 3 K and 100mJ / cm 3 K.
[0059] 2. Test the porous La-Fe-Si-based magnetic refrigeration material La obtained in step 6) using an electronic universal testing machine 0.7 Ce 0.3 Fe 11.5 Mn 0.15 Si 1.35 H z The three-point bending load-displacement curve of hydride, such as Figure 5 As shown. The measured sample size is: length 10mm, width 2mm, thickness 0.7mm. The bending strength of the sample is 14.7MPa.
[0060] 3. Use laser thermal conductivity analyzer (LFA) to test the La obtained in step 5). 0.7 Ce 0.3 Fe 11.5 Mn 0.15 Si 1.35 and the porous La-Fe-Si-based magnetic refrigeration material La obtained in step 6) 0.7 Ce 0.3 Fe 11.5 Mn 0.15 Si 1.35 H z Thermal conductivity of hydride. The sample size is 12.5 mm in diameter and 2 mm in thickness. The thermal conductivity of the sample at room temperature is 6.4 W / mK before hydrogenation, and it decreases slightly to 4.9 W / mK after hydrogenation.
[0061] Embodiment 2:
[0062] The general chemical formula of the La-Fe-Si based magnetic refrigeration material of this embodiment is: La 0.7 Ce 0.3 Fe 13.68 Si 1.6 H z .
[0063] Scanning electron microscope was used to observe the La-Fe-Si based magnetic refrigeration material of this embodiment before hydrogen charging. 0.7 Ce 0.3 Fe 13.68 Si 1.6The microstructure of the sample, such as Figure 1 As shown in Figure 2, it can be seen that the sample is composed of multiple magnetocaloric phases, multiple pores and non-magnetocaloric phases. The magnetocaloric phase is NaZn 13 La(Fe,Si) type crystal structure 13 The base phase (gray area) is connected to each other to form an integrated structure, and the volume fraction of the magnetocaloric phase is about 72%. The non-magnetocaloric phases of this embodiment are mainly α-(Fe, Si) (black area) and La-Ce-rich rare earth alloy (white area). It can be seen that the α-(Fe, Si) phase is relatively coarse and has a high content. The density of the sample obtained by the Archimedean drainage method is 6.33g / cm 3 The porosity of the sample is 12%. The block sample of the porous structure still maintains its complete shape after being filled with hydrogen, and there is no obvious crack in the appearance.
[0064] The preparation method of the La-Fe-Si based magnetic refrigeration material of this embodiment comprises the following steps in sequence:
[0065] 1) Press La 1.4 Ce 0.6 Fe 11 Si2 chemical formula ingredients are loaded into the crucible of a vacuum induction melting furnace, and high-purity argon gas is filled in after evacuation. When the temperature rises to the point where the raw materials are completely melted and the alloy melt is uniform, the alloy liquid is poured into a copper mold to form an alloy ingot;
[0066] 2) mechanically crushing and screening the alloy ingot prepared in step 1);
[0067] 3) The powder with a particle size of ≤38 μm sieved in step 2) was mixed with pure Fe powder and Si powder according to La 0.7 Ce 0.3 Fe 13.68 Si 1.6 The chemical formula is prepared into a mixed powder, poured into a mold, and pressed into a green body at room temperature in a nitrogen atmosphere with a pressure of 1000MPa;
[0068] 4) La pressed in step 3) 0.7 Ce 0.3 Fe 13.68 Si 1.6 The green body is placed in a quartz tube, which is then evacuated, filled with argon gas, and sealed;
[0069] 5) Place the sealed quartz tube in step 4) into an annealing furnace, heat to 1080°C, and anneal for 3 days to form a NaZn 13 La of magnetocaloric phase 0.7 Ce 0.3 Fe 13.68 Si 1.6 alloy;
[0070] 6) The NaZn prepared in step 5) 13 La of magnetocaloric phase 0.7 Ce 0.3 Fe 13.68 Si 1.6 The alloy was filled with hydrogen to saturation in a hydrogen atmosphere at 300°C and 0.2 MPa to obtain a porous La-Fe-Si-based magnetic refrigeration material La 0.7 Ce 0.3 Fe 13.68 Si 1.6 H z Hydride.
[0071] Physical performance test:
[0072] 1. The porous La-Fe-Si-based magnetic refrigeration material La obtained in step 6) was measured using a superconducting quantum interference vibrating sample magnetometer MPMS (SQUID) VSM 0.7 Ce 0.3 Fe 13.68 Si 1.6 H z Thermomagnetic (MT) curves and isothermal magnetization (MH) curves at different temperatures. Figure 2 It can be seen that the Curie temperature of the material is 318K. Figure 3 As shown in the figure, near the Curie temperature, the sample magnetization curve has an obvious inflection point, showing a first-order paramagnetic to ferromagnetic magnetic transition. According to Maxwell's relationship:
[0073]
[0074] The entropy change under different temperature and magnetic field changes is calculated from the rising field isothermal magnetization curve. Figure 4 It can be seen that low magnetic field can cause the porous material to produce a large entropy change. The maximum entropy changes under 0-1T and 0-2T magnetic fields are 7.4J / kgK and 11.7J / kgK, respectively. It is further obtained that the maximum volume entropy changes under 0-1T and 0-2T magnetic fields are 47mJ / cm 3 K and 74mJ / cm 3 K.
[0075] 2. Test the porous La-Fe-Si-based magnetic refrigeration material La obtained in step 6) using an electronic universal testing machine 0.7 Ce 0.3 Fe 13.68 Si 1.6 H z The three-point bending load-displacement curve is as follows: Figure 5 The sample size is as follows: length 10 mm, width 2 mm, thickness 0.7 mm. The bending strength of the sample is 16.5 MPa.
[0076] 3. Test the porous La-Fe-Si-based magnetic refrigeration material La obtained in step 6) using a laser thermal conductivity analyzer (LFA) 0.7 Ce 0.3 Fe 13.68 Si 1.6 H z Thermal conductivity of hydride. The sample size is 12.5 mm in diameter and 2 mm in thickness. The thermal conductivity of the sample is 3.7 W / mK at room temperature.
[0077] The Ce in the above embodiment can be replaced in whole or in part by one or two of Pr and Nd, and the Mn can be replaced in whole or in part by one or two of Cr, Co, Ni, Al or a combination of two or more, as long as NaZn can be formed. 13 The structure is of type, and the various magnetic heat phases contained in the La-Fe-Si based magnetic refrigeration material are connected to form an integrated structure and pores. 13 La(Fe,Si) type crystal structure 13 Chemical formula of base phase: R x (Fe 1-a M a ) 13- y Si y A z , wherein R is selected from La only; or any one or a combination of two or more of Ce, Pr, Nd elements and La; M is selected from Cr, Mn, Co, Ni, Al elements or a combination of two or more; A is selected from H element only; or one or a combination of two of B and C and H element, x satisfies: x=1, y satisfies: 1≤y≤2, z satisfies: 0.1≤z≤3, a satisfies: 0≤a≤0.1.
Claims
1. A La-Fe-Si based magnetic refrigeration material, comprising a plurality of magnetocaloric phase units and a plurality of pore units, characterized in that: The magnetocaloric phase is NaZn 13 La(Fe,Si) type crystal structure 13 The base phase, each of the magnetocaloric phase units is connected to form an integrated structure.
2. The La-Fe-Si based magnetic refrigeration material according to claim 1, characterized in that: It also includes a non-magnetocaloric phase, and the La-Fe-Si based magnetic refrigeration material is composed of a magnetocaloric phase unit, a pore unit and a non-magnetocaloric phase unit, and the non-magnetocaloric phase is one or more combinations of Fe, Fe alloy, and rare earth alloy.
3. The La-Fe-Si based magnetic refrigeration material according to claim 1, characterized in that: The NaZn 13 La(Fe,Si) type crystal structure 13 Chemical formula of base phase: R x (Fe 1-a M a ) 13-y Si y A z , wherein R is selected from La only; or any one or a combination of two or more of Ce, Pr, Nd elements and La; M is selected from Cr, Mn, Co, Ni, Al elements or a combination of two or more; A is selected from H element only; or one or a combination of two of B and C and H element, x satisfies: x=1, y satisfies: 1≤y≤2, z satisfies: 0.1≤z≤3, a satisfies: 0≤a≤0.
1.
4. The La-Fe-Si based magnetic refrigeration material according to any one of claims 1 to 3, characterized in that: In the La-Fe-Si based magnetic refrigeration material, the porosity P of the pores satisfies: 0<P<20%.
5. The La-Fe-Si based magnetic refrigeration material according to claim 4, characterized in that: The maximum volume entropy change of the La-Fe-Si-based magnetic refrigeration material under a 2T magnetic field change is ≥60mJ / cm 3 K, thermal conductivity at room temperature ≥3W / mK, flexural strength at room temperature ≥10MPa.
6. A method for preparing the La-Fe-Si based magnetic refrigeration material according to any one of claims 1 to 5, characterized in that: The following steps are included in sequence: 1) According to R x (Fe 1-a M a ) (13-y)b Si y A z Chemical formula configuration raw materials; wherein R is selected from only La; or any one or a combination of two or more of Ce, Pr, Nd elements and La; M is selected from any one or a combination of two or more of Cr, Mn, Co, Ni, Al elements; A is selected from one or a combination of two of B and C, x satisfies: 0.8≤x≤1.2, y satisfies: 1≤y≤2, z satisfies: 0≤z≤0.5, a satisfies: 0≤a≤0.1, b satisfies: 1≤b≤2; 2) melting the raw materials prepared in step 1) to form an alloy, and then crushing the alloy into particles; 3) pressing the crushed particles obtained in step 2) into a green body; 4) Annealing the compacted body in step 3) to obtain NaZn 13 Phase of type crystal structure; 5) The green body after annealing in step 4) is subjected to hydrogen charging treatment.
7. The preparation method according to claim 6, characterized in that: In step 3), the particle size d of the particles satisfies: d≤300 μm.
8. A method for preparing the La-Fe-Si based magnetic refrigeration material according to any one of claims 1 to 5, characterized in that: The following steps are included in sequence: 1) According to R x Fe 13-y Si y Chemical formula configuration raw materials; wherein R is selected from only La; or any one or a combination of two or more of Ce, Pr, Nd elements and La, x satisfies: 1≤x≤7, y satisfies: 1≤y≤10; 2) melting the raw materials prepared in step 1) to form an alloy, and then crushing the alloy into particles; 3) The crushed particles in step 2) are used as intermediates and mixed with Fe powder and Si powder; or, mixed with Fe powder, Si powder and alloy powder according to R x (Fe 1-a M a ) (13-y)b Si y A z The mixed powder is prepared according to the chemical formula, wherein the alloy powder is a binary or multi-element alloy powder composed of Fe and Cr, Mn, Co, Ni, Al, B, C, and Si; R is selected from La only; or any one or a combination of two or more of Ce, Pr, and Nd elements and La; M is selected from any one or a combination of two or more of Cr, Mn, Co, Ni, and Al elements; A is selected from one or a combination of two of B and C, x satisfies: 0.8≤x≤1.2, y satisfies: 1≤y≤2, z satisfies: 0≤z≤0.5, a satisfies: 0≤a≤0.1, and b satisfies: 1≤b≤2; 4) pressing the mixed powder in step 3) into a green body; 5) annealing the compacted body obtained in step 4) to obtain a NaZn 13 Phase of type crystal structure; 6) The green body after annealing in step 5) is subjected to hydrogen charging treatment.
9. The preparation method according to claim 8, characterized in that: In step 3), R x Fe 13-y Si y The particle size of the alloy particle intermediate is ≤300 μm.
Citation Information
Patent Citations
Rear earth refrigeration material having large magnetic heating effect and preparation thereof
CN101477864A
Magnetic refrigeration material and method for manufacturing magnetic refrigeration material
CN103814144A
Method for manufacturing magnetic material
JP2005120391A
